Ambidextrous Organization: Literature Review - Diana Mana-Ay; Akash Kashyap; Jawad Bin Forhad; Talat Darakhshan (Har Press Indonesia, 2020)
Among the current concepts suggested for managers to deal with turbulence and multidimensionality in the business climate, organizational ambidexterity is listed. It seems to be quite enticing but difficult to incorporate the idea of incorporating both evolutionary and innovative organizational changes. While it has been widely debated for more than twenty years in management-related literature, it has not been extensively explored and is still an important subject for further research. The purpose of the paper is to examine the contribution of literature to the advancement of the idea of ambidextrous organization and recognize the major problems and trends in research production. The research method aims to address the following questions: (1) What are the main contributions of literature in the field to the concept's development? (2) What are the key topics of study and developments in the field? The applied methodology is a systematic literature survey. For the sampling process, the Scopus database is used as a source. The analysis highlights the following main areas of research interest in the field: (1) ambidexterity and ambidextrous conceptualization of organizations, (2) context of organizational management (including managers) where these assumptions are embedded and studied, (3) innovations, processes of organizational learning and creativity, and (4) aspects of strategic management.